Роль альтернативних фінансових інститутів у розвитку інноваційних механізмів оптимізації управління капіталом сільськогосподарських підприємств - Качула, Світлана Валентинівна; Kachula, Svitlana; Хоруженко, Дмитро Олександрович; Khoruzhenko, Dmytro (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
У статті досліджено роль альтернативних фінансових інститутів у розвитку інноваційних механізмів оптимізації управління капіталом сільськогосподарських підприємств. Капітал агропідприємства розглядається як інтегральний ресурс, що поєднує фінансові, матеріальні, земельні та інтелектуальні складові, здатні забезпечувати стабільність і розвиток у мінливих ринкових умовах. Показано, що альтернативні фінансові інститути, включаючи кредитні спілки, страхові компанії, лізингові та факторингові структури, венчурні та краудфандингові платформи, створюють додаткові джерела фінансування, знижують ризики та сприяють диверсифікації капіталу. Особлива увага приділена впровадженню цифрових технологій, фінтех-рішень і партнерських моделей фінансування для підвищення ефективності управління ресурсами. За допомогою проведеного аналізу, систематизовано проблеми, перспективи та напрями подальших досліджень у сфері фінансового забезпечення аграрного сектору. The article examines the role of alternative financial institutions in the development of innovative mechanisms for optimizing capital management in agricultural enterprises. Agricultural capital is defined as an integrated resource combining financial, material, land, human, and intellectual components, which ensures the stability, sustainability, and competitiveness of enterprises under dynamic and volatile market conditions. It is demonstrated that alternative financial institutions, including credit unions, insurance companies, leasing and factoring firms, venture funds, and crowdfunding platforms, provide additional financing channels, reduce financial risks, and contribute to the diversification and efficient utilization of capital. The study emphasizes the implementation of digital technologies, fintech solutions, and partnership-based financial models as tools for improving the efficiency of capital management. Analytical tables and diagrams are presented to systematize existing problems, prospects, and practical approaches to integrating alternative financial instruments into agricultural capital management practices. The research highlights the potential of alternative financial institutions to strengthen financial resilience, support investment in innovative technologies, and promote sustainable development in the agrarian sector. Furthermore, the article identifies unresolved issues, including the optimization of financial structures, regulatory support, and the development of effective institutional frameworks, which require further investigation to enhance the practical application of alternative financial mechanisms in agricultural enterprises. The findings contribute to the theoretical understanding and offer practical recommendations for stakeholders seeking to implement innovative financial strategies aimed at maximizing resource efficiency and long-term enterprise growth.
The role of alternative financial institutions in the development of innovative mechanisms for optimizing capital management in agricultural enterprises
Keywords: альтернативні фінансові інститути; alternative financial institutions; інноваційні механізми; innovative mechanisms; оптимізація управління капіталом; capital management optimization; сільськогосподарські підприємства; agricultural enterprises; фінансові інструменти; financial instruments; фінансовий менеджмент; financial management; небанківський фінансовий сектор; non-banking financial sector